Strategi Pemasaran: Implementasi Promosi Word of Mouth Terhadap Minat Nasabah Memilih Produk Bank - Radlyah Hasan Jan; Fitria Ayu Lestari Niu; Putri Oktavia Mokoginta (J-MAS (Jurnal Manajemen dan Sains), 2023)
The existence of competition in the banking industry in marketing products and forming customer interest in choosing banking products is a major challenge. The various marketing strategies that are common and often implemented by banks include promotional media such as pamphlets, brochures, advertisements, mass media, social media, and so on. Other promotional media are considered very effective, namely, communication media commonly called Word of Mouth (WoM) communication. The Prisma Dana Bank Kotamobagu Branch seems to lack promotion of its products. However, many people are interested in using credit loans and saving products of Prisma Dana Bank Kotamobagu Branch, so this study aims to describe the implementation of the Word of Mouth promotion strategy towards customer interest in customer interest in choosing products Prisma Dana Bank Kotamobagu Branch by using descriptive qualitative methods. Data was collected through the stages of direct observation in the field, direct interviews with informants consisting of leaders, employees, and customers, and documentation in the relevant literature, documents, and results of previous studies. The data that has been collected is then analyzed through the stages of data reduction, data display, and conclusion. The results show that the thing that forms Word of Mouth among customers is the satisfaction obtained from the services and benefits from the products provided by Prisma Dana Bank Kotamobagu Branch to its customers in the form of recommendations and testimonials from the customer’s experiences to friends, relatives, and family. In other words, the higher the level of customer satisfaction, the more the Word of Mouth promotion is formed and runs among the public. Service quality and product benefits can build interest and directly promote Word of Mouth promotional communication between customers through customer satisfaction.